Rethinking Nature’s Rights: An Ethical Framework for Sustainable Coexistence - Halkis, Mhd; Waldani, Izmi (Journal of Ecohumanism, 2024)
This article critically explores the philosophical, ethical, and legal foundations of nature’s rights as a framework for promoting sustainability. It delves into the implications of recognizing ecosystems as legal entities, integrating eco-centric principles that challenge traditional anthropocentric perspectives. The study argues that acknowledging the intrinsic value of nature is essential for creating a sustainable coexistence between human societies and the environment. The article presents a cohesive approach that advocates for incorporating nature’s rights into governance structures and policies by analyzing ecological, ethical, and legal dimensions. It outlines concrete strategies for implementing these principles, emphasizing their role in reshaping policy and practice to better align with environmental conservation goals. Ultimately, the article aims to demonstrate how transforming legal and governance systems can foster a more balanced and ethical relationship between humanity and the natural world, benefiting ecosystems and human communities.